An analysis of factors that affect earnings quality on Islamic commercial banks: The case at Indonesia and Malaysia - Syada Aryanto; Mukhzarudfa Mukhzarudfa; Wiralestari Wiralestari; Amirul Afif Muhamat (Universitas Negeri Surabaya, 2023)
This research aims to determine the impact of leverage, liquidity, and profitability; examine company size as a moderating element; and compare earnings quality at Indonesian and Malaysian Islamic commercial banks. This study's subjects were Indonesian and Malaysian Islamic commercial banks, with a sample size of ten Indonesian Islamic commercial banks and fourteen Malaysian Islamic commercial banks from 2016-2020. The regression approach was employed in this investigation. According to the findings of this study, leverage does not affect earnings quality; liquidity hurts earnings quality; profitability does not affect earnings quality; company size is unable to moderate the relationship of leverage to earnings quality; company size is unable to moderate the relationship of liquidity to earnings quality; company size is unable to moderate the relationship between profitability and earnings quality; Leverage, liquidity and profitability simultaneously have no effect on earnings quality at Indonesian Islamic commercial banks, but simultaneously affect Malaysian Islamic commercial banks; and there is no difference in earnings quality at Indonesian and Malaysian Islamic commercial bank.